The Effect of Soyabean Extender on Viability and DNA Integrity of Kintamani Dog Sperm on Cold Storage - Pradana, I Made Yoga Windu; Bebas, Wayan; Puja, I Ketut (Veterinary Science and Medicine Journal, 2016)
The objective of this study was to evaluate the viability and integrity of canine semen diluted in egg yolk glucose-citrate and Tris-citrate-glucose-soya bean. Semen was collected by manual manipulation from an apparently healthy kintamani dog stud. The semen was subjected to gross and microscopic examination to determine its viability following dilution in different extenders. Only semen with motility rate of 60% or higher was used in this study. Semen samples were diluted in Tris-citrate-glucose-soya bean and egg yolk glucose-citrate extenders at two levels of dilution; sperm to extenders ratio of 1:2 and 1:3. Following semen dilution, evaluations were made on sperm motility, percentage of live sperm, and DNA integrity at 0 hour, 3 hours, and 6 hours under 5 o C of storage. Data was analyzed by multivariate analysis of variance (MANOVA).The present results showed a high significant different (p<0.01) in sperm motility, percentage of live and DNA integrity between treatment with egg yolk glucose-citrate and Tris-citrate-glucose-soya bean.  The result also showed that percentage of live sperm and DNA integrity of semen at 1:2 dilution difference significantly (p<0.01) to that of 1:3 dilution. The sperm viability and integrity were significantly difference (p<0,01) between the duration of storage at 5°C. Thus, the current study indicated that Tris-citrate-glucose- soya bean extenders  was sufficient to maintain motility, viability, and DNA integrity of kintamani dog  spermatozoa during storage at 5 o C. Further research should be conducted to evaluate the fertility of spermatozoa following dilution with these extenders.
Keywords: viability; DNA integrity; semen; kintamani dog